How is financial reporting fraud with the fraud hexagon approach before and during Covid-19 pandemic? - Dedik Nur Triyanto; Mirza Aulia Nur Fajri; Dhian Wahyuni (Journal of Contemporary Accounting, 2023)
This study investigates the impact of fraud hexagons on financial statement fraud in property and real estate sector companies listed on the Indonesian stock exchange before and after the covid-19 outbreak. The study's sample size was 168 data points. To evaluate the hypothesis, the data analysis approach employs logistic regression, as well as sample paired t-tests and the McNemar test. The findings revealed that financial statement fraud was influenced by pressure, rationalization, and capability. Meanwhile, chance, arrogance, and collaboration have little effect on financial statement fraud. The disparity in values between before and during the covid-19 epidemic had a substantial impact on financial stability. Other factors, on the other hand, indicate no significant differences in value when comparing before and after the Covid-19 epidemic. This study has consequences for stakeholders, the government, and the general public in terms of being aware of the likelihood of fraud when a phenomenon such as the covid-19 epidemic occurs.